'Hot', 'Cold' and 'Warm' supports: towards theorising where refugee students go for assistance at university. Issue 1 (2nd January 2018) - Baker, Sally; Ramsay, Georgina; Irwin, Evonne; Miles, Lauren
ABSTRACT: This paper contributes a rich picture of how students from refugee backgrounds navigate their way into and through undergraduate studies in a regional Australian university, paying particular attention to their access to and use of different forms of support. We draw on the conceptualisation of 'hot' and 'cold' knowledge, offered by Ball and Vincent (1998. "'I Heard it on the Grapevine': 'Hot' Knowledge and School Choice." British Journal of Sociology of Education 19 (3): 377–400), and the addition of 'warm' knowledge offered by Slack et al. (2014. "'Hot', 'Cold' and 'Warm' Information and Higher Education Decision Making." British Journal of Sociology of Education 35 (2): 204–223), to develop an understanding of how students from refugee backgrounds make choices about how they locate, select and access support for their studies. The findings of this paper suggest that students from refugee backgrounds do not view the 'cold' (unfamiliar-formal) institutional support on offer as 'for them'; instead they expressed a preference for the 'warm' (familiar-formal) support offered via 'trusted' people who act as literacy/sociocultural brokers or 'hot' (familiar-informal) support of their grapevine of other students (past and present) or experienced community members.